Influence of NFV introduction on core network element and planning method - Yuan ZHAO; Jiyan WANG (Dianxin kexue)
Network function virtualization (NFV) is an obvious change in communication technology,especially for the core network.Firstly,the two level changes between the most obvious and the most far-reaching about element and network construction methods were illustrated and analyzed.In addition,the core network planning generally included the capacity planning and network planning,was closely related to both the NFV cloud,with the decoupling of hardware and software of network element,would change the planning method.Based on this,the effect of NFV on core network element and its planning method in many aspects were illustrated.